2021
DOI: 10.1002/qua.26824
|View full text |Cite
|
Sign up to set email alerts
|

Computational insights into themulti‐Diels–Alderreactions of neutralC60and its Li+encapsulated analogue: A density functional theory study

Abstract: The exohedral functionalization of encapsulated fullerenes (such as Diels-Alder reaction) gives rise to wide-ranging derivatives that are useful for potential applications.Though the oligo-adducts have significant uses in material and biological sciences, they are hardly investigated due to experimental limitations. To shed light on that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(78 reference statements)
0
3
0
Order By: Relevance
“… 36 Similar results were obtained by Das et al in the successive DA cycloadditions of 1,3-butadiene to the [6,6] bonds of C 60 and Li + @C 60 . 37 …”
Section: Introductionmentioning
confidence: 99%
“… 36 Similar results were obtained by Das et al in the successive DA cycloadditions of 1,3-butadiene to the [6,6] bonds of C 60 and Li + @C 60 . 37 …”
Section: Introductionmentioning
confidence: 99%
“…The analysis of fullerene reactivity as dienophiles in Diels-Alder cycloadditions has been investigated both experimentally and theoretically [1,2,4,[22][23][24][25][26][27][28]. The pioneering computational work of Fujimoto and co-workers suggested that the double addition of butadiene to C 60 is not highly regioselective [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some well-known examples include the commercially available IC60MA (indene C60 mono adduct) and IC60BA (indene C60 bis adduct) [16,20], and also the analogous C70 compounds, IC70MA and IC70BA [16,21]. The analysis of fullerene reactivity as dienophiles in Diels-Alder cycloadditions has been investigated both experimentally and theoretically [1,2,4,[22][23][24][25][26][27][28]. The pioneering computational work of Fujimoto and co-workers suggested that the double addition of butadiene to C60 is not highly regioselective [22].…”
Section: Introductionmentioning
confidence: 99%